Hierarchical spatial structure and levels of resolution of intertidal grazing and their consequences on predictability and stability at small scales - Diaz Diaz, Eliecer Rodrigo (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2009)
The aim of this research was to assess three hierarchical aspects of alga-grazer interactions in intertidal communities on a small scale: spatial heterogeneity, grazing effects and spatial stability in grazing effects. First, using semivariograms and cross-semivariograms I observed hierarchical spatial patterns in most algal groups and in grazers. However, these patterns varied with the level on the shore and between shores, suggesting that either human exploitation or wave exposure can be a source of variability. Second, grazing effects were studied using manipulative experiments at different levels on the shore. These revealed significant effects of grazing on the low shore and in tidal pools. Additionally, using a transect of grazer exclusions across the shore, I observed unexpected hierarchical patchiness in the strength of grazing, rather than zonation in its effects. This patchiness varied in time due to different biotic and abiotic factors. In a separate experiment, the effect of mesograzers effects were studied in the upper eulittoral zone under four conditions: burnt open rock (BOR), burnt pools (Bpool), non-burnt open rock (NBOR) and non-burnt pools (NBpool). Additionally, I tested spatial stability in the effects of grazing in consecutive years, using the same plots. I observed great spatial variability in the effects of grazing, but this variability was spatially stable in Bpools and NBOR, meaning deterministic and significant grazing effects in consecutive years on the same plots. Both the significance in grazing effects and spatial stability depended on the level of resolution (species, functional, biomass) at which the algal assemblage was evaluated, suggesting hierarchical variability. In order to be able to predict spatial variability in the effects of grazers in the upper eulittoral zone using biotic and abiotic micro- and macrofactors, a conceptual model was proposed, based on data from several multiple-regressions. This linked the interactions among three elements: idiosyncratic heterogeneity, micro and macrofactors. This suggests that spatial variability can be a product of these factors, while spatial stability can be caused by the same or different combinations of factors. In conclusion, grazing and other ecological phenomena must be studied hierarchically, not only through spatiotemporal scales, but also at different levels of resolution, as these also influence our perception of patterns.
Keywords: Marine algae -- Effect of grazing on; Shorelines -- South Africa; Zostera marina; Intertidal ecology; Spatial analysis (Statistics)